Efeitos do Condicionamento Sobre a Função Ventricular Esquerda de Equinos Jovens da Raça Puro Sangue Árabe - Ramos, Gabriel Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Physical conditioning promotes changes in homeostasis that lead to significant metabolic alterations in various systems, including the cardiovascular system. In horses, several studies have evaluated protocols based on plasma lactate concentrations; however, few authors have analyzed their influence on cardiac function. This present study aims to investigate the adaptive responses to the left ventricular (LV) function of young horses, assessed at rest and immediately after a physical stress test (TStress), induced by six weeks of physical conditioning based on the external load necessary to achieve a plasma lactate concentration of 2 mmol/L (V2). Fourteen young Arabian Thoroughbred horses, with an average age of 28.42 ± 3.75 months and no prior history of physical conditioning, were used in this study. The animals were evaluated through echocardiography performed at rest and immediately after TStress, both before and after a six-week conditioning period based on V2 determined by an incremental exercise test (IET) on a treadmill. There was an improvement in the aerobic capacity of the animals, as evidenced by the increase in V2 (5.214 ± 0.328 vs. 6.763 ± 0.434) and V4 (5.857 ± 0.42 vs. 7.691 ± 0.549) (p <0.001) after the conditioning period. There were also reductions in resting heart rate (HR) and the maximum HR reached during TStress (p < 0.001). Conditioning led to a reduction in the internal diameter associated with increases in the thickness of the interventricular septum, posterior wall, average thickness, and LV mass (p < 0.05). The evaluation performed after TStress in conditioned animals revealed increases in integral time-velocity (ITV), stroke volume (SV), systolic indices (SI) and cardiac indices (CI), ejection times (ET) and deceleration times (DT), end-diastolic volume (EDV), time to the onset of radial myocardial velocity during the early diastolic phase (tEm), and time to maximum transmitral flow velocity (tEA), with reductions in preejection period (PEP) and PEP/ET ratios, circumferential velocity of myocardial fibers (Vcf). The conditioning protocol was capable of improving the aerobic capacity of the animals and promoting cardiac remodeling associated with improved left ventricular function.

– O condicionamento físico promove alterações na homeostase que levam a alterações metabólicas importantes em diversos sistemas, dentre eles o sistema cardiovascular. Nos equinos, diversos estudos avaliaram protocolos baseados nas concentrações plasmáticas de lactato, entretanto, poucos autores analisaram a influência destes sobre a função cardíaca. O presente trabalho tem como objetivo estudar as respostas adaptativas sobre a função do ventrículo esquerdo (VE) de equinos jovens, avaliada em repouso e imediatamente após teste de estresse físico (TStress), promovidas pelo condicionamento físico de seis semanas baseado na carga externa necessária para obter concentração plasmática de lactato igual a 2 mmol/L (V2). Foram utilizados 14 equinos da raça Puro Sangue Árabe jovens, com idades de (média ± dp) 28,42 ± 3,75 meses, sem histórico de condicionamento físico. Os animais foram avaliados por meio da ecocardiografia realizada em repouso e imediatamente após TStress feita antes e após período de condicionamento de seis semanas baseado na V2 determinada por teste de esforço incremental (TEI) realizado em esteira rolante. Houve melhora na capacidade aeróbia dos animais haja vista o aumento da V2 (5,214 ± 0,328 vs. 6,763 ± 0,434) e V4 (5,857 ± 0,42 vs. 7,691 ± 0,549) (p < 0,001) após o período de condicionamento. Houve também reduções da frequência cardíaca (FC) em repouso e da maior FC atingida durante o TStress (p <0,001). O condicionamento promoveu redução no diâmetro interno associado a aumentos nas espessuras do septo interventricular, parede posterior, espessura média e massa do VE (p < 0,05). A avaliação realizada após TStress nos animais condicionados revelou aumentos na integral tempo-velocidade (ITV), volume ejetado (Vej), índices sistólico (IS) e cardíaco (IC), tempos de ejeção (TEj) e desaceleração (TD), volume diastólico final (VDF), tempo para o início da velocidade miocárdica radial durante a fase diastólica inicial (tEm) e tempo para a máxima velocidade do fluxo trasmitral (tEA) com reduções no período pré-ejeção (PPE) e nas razões PPE/TEj, velocidade circunferencial das fibras miocárdicas (Vcf). O protocolo de condicionamento foi capaz de melhorar a capacidade aeróbia dos animais e promover o remodelamento cardíaco associado à melhora da função ventricular esquerda.
Effects of Conditioning on the Left Ventricular Function of Young Purebreed Arabian Horses
Keywords: Ecocardiografia; Esteira rolante; Testes de função cardíaca; Lactato; Treinamento